Caracterização microestrutural da camisa de um alargador de furo de poço de petróleo - Medeiros Filho, Ricardo Hugo Nunes (Universidade Federal Rural do Semi-Árido, 2017)
Petroleum is one of the world's major energy sources, for oil production oil well drilling is required. During drilling of the well, it is necessary to widen the well, for this purpose drills are used directly connected to the drills through the drilling column. The Reamers consist of 5 parts. Cutters, Reamer Pin, Cross Pin, Drive-Fit Body Bearing Blocks and Socket Head Cap Screws and Lock Washers Cutters surround the shaft and contain the uncertainties that promote enlargement. In this work the characterization of a sample of Cutters from an extension provided by Schlumberger Serviços de Petróleo Ltda. Microscopic metallography, hardness and microhardness tests, X-ray diffraction and chemical composition analysis were performed. Three samples were taken from the cutters, two of them being subjected to the treatment of tempera one with cooling in water and another with cooling in oil, in the samples were made the microscopic metallography in order to perform the analysis of the microstructure, these samples were submitted to the hardness and microhardness tests for hardness analysis, since this piece is submitted to intense mechanical wear. In addition Cutters was subjected to X-ray diffraction and analysis of the chemical composition, to determine the steel used in the manufacture of Cutters. Finally, with the methods used it was possible to discover that the steel was SAE 8620 steel, in addition, it is possible to perform a heat treatment in order to increase its resistance to hardness.
Monografia
Keywords: Poço de petróleo; Alargadores; Camisa; SAE 8620; Oil well; Reamers; Cutters; SAE 8620; ENGENHARIAS::ENGENHARIA MECANICA